1991
DOI: 10.3109/03009749109096812
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Dynamic Training in Water for Rheumatoid Arthritis Functional Class II - a Long-term Study of Effects

Abstract: The aim of the study was to assess the effects of once-weekly, intensive dynamic training in water of patients with Rheumatoid Arthritis (RA). Thirty patients with RA, functional class II, in a training group (TG) and 30 in a comparison group (CG) were assessed with respect to clinical, radiological and functional disease manifestations and psychosocial consequences before and after a four-year training period. After the training period the TG patients had significantly better grip strength and higher activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 14 publications
0
45
0
2
Order By: Relevance
“…In contrast, two studies reported no significant reduction in pain following hydrotherapy in adults with arthritis. 41,42 Other studies suggest no additional reduction in pain with hydrotherapy than with immersion to the neck in heated water. 24,43 Nonetheless, these results have clinical relevance, and increased joint pain has been reported as the main reason for patients with rheumatoid arthritis stopping landbased exercises.…”
Section: Consequences Of Pathophysiology Of Jiamentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, two studies reported no significant reduction in pain following hydrotherapy in adults with arthritis. 41,42 Other studies suggest no additional reduction in pain with hydrotherapy than with immersion to the neck in heated water. 24,43 Nonetheless, these results have clinical relevance, and increased joint pain has been reported as the main reason for patients with rheumatoid arthritis stopping landbased exercises.…”
Section: Consequences Of Pathophysiology Of Jiamentioning
confidence: 99%
“…70,72 Therefore, comparing groups, greater improvement was found in both endurance, fitness and the physical aspects of HRQoL in the combined than the land group, in line with findings of smaller hydrotherapy studies in paediatric and adult rheumatological populations. 24,31,42,[48][49][50]54,55 These improvements might be explained by the reduced weightbearing through joints in water, which allows patients to exercise strenuously without pain, risk of injury or stress on articular and soft tissue structures. [45][46][47] Furthermore, deep water running requires less aerobic metabolism and shorter stride length (less strain on joints, especially if articular movement is restricted) than running in shallow water or on land.…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Stenstrom et al (29) seguiram por quatro anos dois grupos de 30 pacientes com diagnóstico de AR. Trinta pacientes realizaram treinamento dinâmico intensivo na água, com freqüência de uma vez por semana durante 40 minutos; o outro grupo não recebeu nenhum treinamento.…”
Section: Hidroterapia Na Aijunclassified
“…The Arthritis Foundation literature states that their aquacize programs are not intended to be a substitute for individualized therapeutic exercise regimens as prescribed by a health care professional (AF, 1996a;AFAP, 1990). These programs are offered as a complement to clinical treatment (Stenstrom et al, 1991).…”
Section: Statemenlpf the Problemmentioning
confidence: 99%